IMPROVISATION: Sygeplejersker på arbejde i Uganda - Martin, Helle Max (Tidsskriftet Antropologi, 2005)
This article is about improvisation, which is a term that nurses in Uganda employ to describe how they overcome the practical difficulties of working in an institutional setting, which lacks the necessary equipment, drugs and staff. On the basis of data from Tororo Hospital in Eastern Uganda, the article explores the meanings of the term improvisation, how it relates to a general discourse about the nursing profession, and how the nurses handle and make sense of a complex and contradictory work situation. Improvisation is a term that both makes customary nursing practice legitimate and supports a professional identity under pressure. It also articulates a nostalgic longing for better times – located both in the past, the golden age of nursing, and in the future since the term improvisation constructs current practice as an interim phenomenon. Thus, “improvisation” offers a way for the nurses to domesticate the contradictory forces, which play a prominent part in nursing in Uganda today.